Comparison of h-index and other bibliometrics in Google Scholar and Scopus for articles published by translational science trainees - Laura D. Davis; Corbyn M. Gilmore; Adriana Vargus; Henry Ogbeifun; Yong-Hee P. Chun; Christopher R. Frei (Humanities & Social Sciences Communications)
Abstract Bibliometrics can help program directors to conduct objective and fair assessments of scholar impact, progress, and collaboration, as well as benchmark performance against peers and programs. However, different academic search engines use different methodologies to provide bibliometric information, so intermixing results from multiple search engines might contribute to inequitable decision-making. Google Scholar and Scopus provide useful bibliometric information for scholars, including the h-index; however, a search of the literature revealed h-index was higher in Google Scholar than Scopus in other scholar populations; therefore, we hypothesized that h-index might also be higher in Google Scholar than Scopus for translational science (TS) trainees. Trained investigators gathered scholarly profile information from Google Scholar and Scopus for all trainees from NIH-supported TS PhD and TS Training (TST) Programs for predoctoral and postdoctoral trainees. Investigators calculated number of citations/year and m-quotient using the data contained therein. M-quotient was defined as h-index divided by “n,” where “n” equaled the number of years since first publication. Investigators used the Wilcoxon Signed Rank test to compare bibliometrics (citations, citations/year, h-index, and m-quotient) from both sources for TS students and trainees. A total of 38 trainees (13 TS PhD students and 26 TST trainees) had active profiles in both Google Scholar and Scopus. Of the TST trainees, 21 were predoctoral and five were postdoctoral trainees. All four metrics (citations, citations/year, h-index, and m-quotient) were significantly higher (p < 0.05) in Google Scholar than Scopus for the entire study population, TS PhD students, TST trainees, and TST predoctoral trainees. All four bibliometrics were numerically higher (but not significantly higher) in Google Scholar than Scopus for TST postdoctoral trainees as well. This is the first study to compare bibliometrics in Google Scholar and Scopus among translational science trainees. We discovered higher overall citation counts in Google Scholar. Significant differences between Google Scholar and SCOPUS in bibliometrics, such as h-index, could impact the decisions made by program directors if the results are intermixed. Stakeholders should be consistent in their choice of academic search engine and avoid cross engine comparisons, as failure to do so might contribute to inequitable decision-making.